Tradisi Pemakaman Keturunan Karaeng (Puang) Di Desa Biring Ere Kecamatan Bungoro Kabupaten Pangkep - Kiki Maya Sari; Dalilul Falihin (UNM Geographic Journal, 2023)
The aims of the study were to find out 1) the existence of the funeral tradition for the descendants of the karaeng (puang) in the people of Biring Ere Village, Bungoro District, Pangkep Regency. 2) The traditional values of the burial of the descendants of the karaeng (puang) in Biring Ere Village, Bungoro District, Pangkep Regency. The type of research used is a qualitative description. Data collection techniques used in this study were interviews, involved observation and documentation. Data analysis used in research is data reduction, data presentation, and conclusions or verification. The results of the study show that: 1) the existence of tradition is maintained because the existence of tradition is maintained by the community through the involvement of the younger generation in carrying out the tradition. The people's belief in the tradition of honoring the deceased. 2) the values contained in the funeral tradition are the values of life that create harmony in society, social values that create mutual cooperation values within the community, psychological values that create inner peace because they have carried out their final obligations and spiritual values that increase faith in the creator